Performance evaluation of ERP implementation by using fuzzy MCDM - (:unkn) unknown (My University, 2011)
In this study, an ERP implementation project risks analysis problem in a Turkish automotive supplier firm is handled. To determine the risk criteria we benefited from the literature, experts and ERP software users. The handled problem is solved by using fuzzy-AHP methodology. Then a sensitivity analysis is performed to evaluate our risk analysis methodology and to validate the results specifically for our case firm. © 2011 IEEE.
Keywords: ERP implementation project; Fuzzy-AHP method; Risk Analysis; Sensitivity Analysis